Short Term Effects of Inner Engineering Completion Online Program on Stress and Well-Being Measures - Upadhyay, Preeti; Joshi, Akshaj; Mishra, Isha; Kelly, Lauren; Novack, Lena; Hariri, Sepideh; Kveraga, Kestutis; Subramaniam, Balachundhar (Frontiers in Psychology, 2022)
Introduction The Covid-19 pandemic has been a major disruptor of routine life, resulting in increased stress and predisposing people to negative outcomes, such as insomnia, anxiety and hopelessness. Mind-body interventions have improved concentration, emotional balance, and positive emotions, with an enhanced sense of productivity, and self-confidence. We therefore hypothesized that exposure to an online mind-body intervention, “Inner Engineering Completion Online (IECO),” would reduce stress and promote well-being. Methods This prospective cohort study enrolled participants registered for the IECO courses, which for the first time were delivered remotely, online. Participants learned a 21-min meditation practice called Shambhavi Mahamudra Kriya during the course, which incorporates controlled breathing and mediation techniques. Each enrolled participant was asked to complete self-reported electronic surveys at three key time points: at the time of consent, immediately after completing IECO, and 6 weeks after IECO completion. Effects of IECO practice were assessed using four well-validated neuropsychological scales: Perceived Stress Scale (PSS), Positive Emotion/Relationship/Engagement Scale (PERMA) Profiler, Pittsburgh Sleep Quality Index (PSQI), and Mindful Attention Awareness Scale (MAAS). A Signed Rank test was used to analyze the survey data and P-values of < 0.05 were considered statistically significant. Results Of the 375 participants interested in participation, 164 participants were eligible. Sixty-eight participants completed surveys at all time points and were identified as compliant participants. The baseline median score for PSS in compliant participants (n = 95) was 13.5 (IQR 9, 18); immediate post-IECO median PSS score was 12 (IQR 8, 16) demonstrating a 1.5 unit decrease in PSS scores (p-value = 0.0023). Similarly, comparing PSS scores in compliant participants (n = 68) for immediate Post IECO [11.5 (IQR 8, 15.5)] to PSS scores at six weeks [8 (IQR 4.5, 12.5)] showed a statistically significant 3.5-unit decrease, indicating a reduction in stress upon routine practice of the intervention (p < 0.0001). Conclusion Incorporating the remotely delivered mind-body intervention Shambhavi Mahamudra Kriya into daily life via the IECO program over as few as 6 weeks produced a significant stress reduction, improvement in sleep quality and mindfulness. Clinical Trial Registration [ClinicalTrials.gov], identifier [NCT04189146].